Debt-for-nature swaps: Axing the debt instead of the forests - Antonie Bauer; Gerhard Illing (Intereconomics, 1992)
Combining debt reduction with halting deforestation seems to be an attractive way of solving two urgent global problems at the same time at hardly any cost. But this view may be overly optimistic. What are the advantages and the drawbacks of debt-for-nature swaps? Are there any better alternatives?
Keywords: 330; Environment